2018
DOI: 10.1111/ejn.14093
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral delta opioid receptors mediate duloxetine antiallodynic effect in a mouse model of neuropathic pain

Abstract: Peripheral delta opioid (DOP) receptors are essential for the antiallodynic effect of the tricyclic antidepressant nortriptyline. However, the population of DOP-expressing cells affected in neuropathic conditions or underlying the antiallodynic activity of antidepressants remains unknown. Using a mouse line in which DOP receptors were selectively ablated in cells expressing Nav1.8 sodium channels (DOP cKO), we established that these DOP peripheral receptors were mandatory for duloxetine to alleviate mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 53 publications
6
20
0
Order By: Relevance
“…Our data also revealed that changes in the expression profile of peripheral DOP receptors correlated with mechanical allodynia. Indeed, we observed decreased DOP receptor expression in unmyelinated calcitonin gene-related peptide (CGRP) positive neurons and free nerve endings in the skin and increased surface expression in the neurons still expressing the receptor in neuropathic conditions but not in mice chronically treated with duloxetine after cuff surgery (Ceredig et al, 2018). Here, we sought to determine whether the same mechanisms are triggered by chronic treatment with the β2 adrenergic agonist formoterol by identifying changes in the expression of peripheral DOP receptor using a mouse line in which peripheral DOP receptors are selectively ablated in neurons expressing the Nav1.8 sodium channel (DOP cKO; Gaveriaux-Ruff et al, 2011) and a knock-in mouse line expressing DOP receptors fused to the green fluorescent protein eGFP (DOPeGFP;Scherrer et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Our data also revealed that changes in the expression profile of peripheral DOP receptors correlated with mechanical allodynia. Indeed, we observed decreased DOP receptor expression in unmyelinated calcitonin gene-related peptide (CGRP) positive neurons and free nerve endings in the skin and increased surface expression in the neurons still expressing the receptor in neuropathic conditions but not in mice chronically treated with duloxetine after cuff surgery (Ceredig et al, 2018). Here, we sought to determine whether the same mechanisms are triggered by chronic treatment with the β2 adrenergic agonist formoterol by identifying changes in the expression of peripheral DOP receptor using a mouse line in which peripheral DOP receptors are selectively ablated in neurons expressing the Nav1.8 sodium channel (DOP cKO; Gaveriaux-Ruff et al, 2011) and a knock-in mouse line expressing DOP receptors fused to the green fluorescent protein eGFP (DOPeGFP;Scherrer et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Sham and Cuff groups both received control saccharin solution 0.2% in drinking water. Sham and Cuff groups were identical to those published previously in Ceredig et al (2018).…”
Section: Treatment Proceduresmentioning
confidence: 99%
See 3 more Smart Citations